Pengembangan Kemampuan Kognitif dan Sosial-Emosional Melalui Penerapan Media Balok dan Bermain Peran Pada Siswa TK Kuntum Mekar, Lampung - Dea, Leli Fertiliana; Latipah, Eva (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2017)
This study aims to (1) to determine the use of block media in the cognitive and social development of children in Kuntum Mekar 2 Bandar Lampung, (2) to know the application of bemain role method in developing cognitive and social emotional of children in Kuntum Mekar Kindergarten 2 Bandar Lampung, (3) to know the successful application of block media and role playing method in early childhood cognitive and social development. This research uses qualitative research method, the data obtained through observation to know the initial data of application of block media and the application of role play, interview to get data in condition of cognitive development and social emotional of early child, then the data is analyzed by data reduction, data presentation and concluded. From the analysis of the research, it can be concluded that: First, the application of beam media in Kuntum Mekar TK 2 Bandar Lampung succeeded. Use the following steps: (a) The teacher prepares the tools. (b) The teacher accepts the children present. (c) Master explains how to play blocks. (d) The child builds with the beam and the teacher is just watching. Second, the application of role playing in Kuntum Mekar 2 Bandar Lampung was successful. Apply using the following steps: (a) Teachers collect children for direction and rules in the game, (b) Teacher discusses the tools to be used, (c) Teacher gives assignments to the child. Third, the successful application of beam media and role playing methods in early childhood cognitive and social development is evidenced by children developing as expected, as children are able to recognize objects by function, the child is able to classify objects by shape, color and size, the child is able to recognize the ABC pattern , children are able to recognize the concept of numbers, children are able to say a lot of objects 1-10 and children are able to cooperate with friends, children are able to know etiquette and courtesy in accordance with local social cultural values, children are able to understand the rules and discipline and children are able to show empathy attitude.